“I Want It All, and I Want It Now”: Lifetime Prevalence and Reasons for Using and Abstaining from Controlled Performance and Appearance Enhancing Substances (PAES) among Young Exercisers and Amateur Athletes in Five European Countries - Lazuras, Lambros; Barkoukis, Vassilis; Loukovitis, Andreas; Brand, Ralf; Hudson, Andy; Mallia, Luca; Michaelides, Michalis; Muzi, Milena; Petróczi, Andrea; Zelli, Arnaldo (Frontiers in Psychology, 2017)
Doping use in recreational sports is an emerging issue that has received limited attention so far in the psychological literature. The present study assessed the lifetime prevalence of controlled performance and appearance enhancing substances (PAES), and used behavioural reasoning theory to identify the reasons for using and for avoiding using controlled PAES in young exercisers across five European countries, in the context of the "SAFE YOU" Project. Participants were 915 young amateur athletes and exercisers (M = 21.62; SD = 2.62) from Cyprus, Germany, Greece, Italy and UK who completed an anonymous questionnaire that included measures of self-reported use of controlled PAES, as well as reasons for using and not using controlled PAES. The results of the descriptive analyses demonstrated that almost 1 out 5 exercisers in the sample had a previous experience with controlled PAES. Higher prevalence rates were found in Greece and Cyprus and lower in Italy. The most frequently reported reasons for using controlled PAES included achieving the desired results faster; pushing the self to the (physical) limits; and recovering faster after exercise/training. Furthermore, the most frequently reported reasons for not using controlled PAES involved worry about any possible adverse health effects; not feeling the need for using them; and wanting to see what can be achieved naturally without using any controlled PAES. The findings of the present study indicate that the use of controlled PAES is fast becoming a crisis in amateur sports and exercise settings and highlight the need for preventive action and concerted anti-doping education efforts.